The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1037/pas0000319
|View full text |Cite
|
Sign up to set email alerts
|

Wechsler Adult Intelligence Scale-Fourth Edition (WAIS-IV) processing speed scores as measures of noncredible responding: The third generation of embedded performance validity indicators.

Abstract: Research suggests that select processing speed measures can also serve as embedded validity indicators (EVIs). The present study examined the diagnostic utility of Wechsler Adult Intelligence Scale-Fourth Edition (WAIS-IV) subtests as EVIs in a mixed clinical sample of 205 patients medically referred for neuropsychological assessment (53.3% female, mean age = 45.1). Classification accuracy was calculated against 3 composite measures of performance validity as criterion variables. A PSI ≤79 produced a good comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 38 publications
3
54
0
Order By: Relevance
“…Prior to consideration, candidates for the study were evaluated by a multidisciplinary team of neurologists, neurosurgeons, and neuropsychologists 31 34 and decisions for surgery were unrelated to study participation. Prospective candidates who displayed cognitive scores that lay outside 1.5 standard deviations of their age-defined means (e.g., WAIS-IV, WCST, and WMS-IV) were excluded 35 , 36 . Consideration for inclusion in the study was only made after patients were scheduled for elective placement of deep brain stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to consideration, candidates for the study were evaluated by a multidisciplinary team of neurologists, neurosurgeons, and neuropsychologists 31 34 and decisions for surgery were unrelated to study participation. Prospective candidates who displayed cognitive scores that lay outside 1.5 standard deviations of their age-defined means (e.g., WAIS-IV, WCST, and WMS-IV) were excluded 35 , 36 . Consideration for inclusion in the study was only made after patients were scheduled for elective placement of deep brain stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…30 Erdodi et al reported high failure rates on validity indices derived from the Wechsler Adult Intelligence Scale (WAIS). 31 A study reporting validity test performance after stroke with initial aphasia found low failure rates on the (standard, pictorial) TOMM measures (7% (1/15 failing trial 2 and 0 failing the retention trial, but high failure rates on the Rey 15-item, RDS (<7) and reliable spatial span (60%, 73% and 40% respectively)). 32 One study described a single case of surgical removal of medial temporal lobe structures, and another described three cases of bilateral hippocampal atrophy after anoxic brain injury; none of these four individuals failed the WMT.…”
Section: Acquired Brain Injurymentioning
confidence: 99%
“…WAIS-IV PSI aggregates the age-adjusted scores on the Symbol Search and Coding subtests 58 and is scaled with a M = 100 and SD = 15. The cut score used in the current project was £ 79, 69 which is just below the ninth percentile.…”
Section: Validating Multi-dimensional Outcome Assessmentmentioning
confidence: 99%